Diet Composition of the Demoiselle Crane (Anthropoides virgo) Migrating Through Lakki Marwat, Pakistan. (December 2013) - Sarwar, Misbah; Hussain, Iftikhar; Khan, Ahmad; Anwar, Maqsood
Demoiselle Cranes (A nthropoides virgo ) migrate through Pakistan between their breeding and wintering grounds. We undertook macro and micro-analyses of 16 gizzards and 35 faecal samples of this elegant bird during its stopovers in the Lakki Marwat area of Khyber Pakhtunkhwa Province, Pakistan. Analysis of 16 gizzards and 16 faecal samples of spring season showed that the bird was predominantly vegetarian and fed on cultivated crops ( viz : wheat, sorghum, chickpea, Egyptian clover and garlic) and wild flora ( viz : wild onion, beard grass and bur clover). Similarly, analysis of 19 faecal samples collected during the autumn revealed the presence of cultivated crops ( viz : chickpea, mustard and spinach) and wild plant species ( viz : wild onion, bur clover, salt cedar, beard grass and alkali seep weed). The Demoiselle Crane supplemented its diet with animal matters (ranging from 3 to 20%) derived from invertebrates belonging to Phylum Arthropoda (Order Pauropodina and Order Plecoptera) and vertebrate species i.e. tadpoles, Mus spp. and nestlings of birds. In addition, large quantities of grit composed of small stones and quartz crystals were found in the gizzards and faecal samples. This study provides information on the important flora and fauna that contribute to the diet of migratory Demoiselle Cranes. This aids strategies to conserve and protect the natural habitats from intensive anthropogenic use and livestock grazing, and helps to sustain and enhance numbers of this avian species.